Socio-Biodiversity Integrative of an Indonesian Oil and Gas Distribution Area as Sustainability-Driven Implementation of Corporate Social Responsibility - Prautama, Cahaya; Wicaksana, Satya Dewastra Bayu; Jumas, Julia Rizki; Uswatun Mujahidah,; Eva Piniji Lestari,; Yunianto Arif Suryawan,; Muchlisah Harliani,; Manshur Rasyid,; Azinuddin Ikram Hakim, (Technium Social Sciences Journal, 2024)
Indonesia, a country rich in natural and human resources, has significant potential for inclusive and sustainable development. The implementation of corporate social responsibility (CSR) programs is a key strategy for oil and gas companies to promote community development through sustainable social-biodiversity initiatives. The regulation of CSR programs under Law No. 40 of 2007, or the Social and Environmental Responsibility Law (TJSL), provides the foundation for companies to commit to socio-biodiversity principles in their CSR efforts. PT Pertamina Patra Niaga FT Lomanis, an oil and gas extraction company, has implemented its CSR commitments in accordance with the TJSL Law, using the achievement of Sustainable Development Goals (SDGs) as a reference for sustainable CSR programs. The methodology of this study includes reporting on community empowerment activities and analyzing qualitative and quantitative data collected during the program's implementation. The findings highlight PT Pertamina Patra Niaga FT Lomanis's commitment to implementing social programs in 2022-2023, including the environmental and social impacts achieved. The overall programs are analyzed in a matrix alignment with the SDGs through the Metadata Development Pillar of Bappenas in the RPJMN 2020-2024. In summary, PT Pertamina Patra Niaga FT Lomanis conducted the Emas Komang program (a community empowerment program based on mangrove ecosystem management) which resulted in social impacts such as increased income for SMEs processing mangroves and the sale of mangrove seedlings, ranging from 4-8 million Rupiah and 12-25 million Rupiah, respectively. Additionally, the program had environmental impacts, including increased mangrove density. The socio-biodiversity CSR program through Emas Komang contributed to the achievement of SDGs points 2, point 8, and point 15, reflecting sustainability goals for 2022-2023.